Legal Consequences of Exploitation in TikTok Live Gift Requests: Konsekuensi Hukum dari Eksploitasi dalam Permintaan Hadiah di TikTok Live - Tri Antika Masruroh; Noor Fatimah Mediawati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rapid growth of social media has generated new forms of online economic activity, including live streaming that enables users to solicit virtual gifts convertible into monetary value. Specific Background: On the TikTok Live platform, such activities have increasingly involved the use of vulnerable groups—elderly persons, children, and individuals with disabilities—raising concerns about public order violations and exploitation resembling online begging. Knowledge Gap: Existing legal studies primarily address exploitation in offline contexts, while juridical analysis linking current regulations to digital gift-solicitation practices remains limited, particularly regarding enforcement and legal responsibility in Indonesia. Aims: This study examines the legal consequences of exploitative gift requests on TikTok Live and identifies relevant regulatory frameworks governing such conduct. Results: Using a normative juridical method with a statutory approach, the research finds that these practices may violate provisions related to begging, child protection, human trafficking prevention, and protection of persons with disabilities, with possible sanctions including criminal penalties, civil liability, and platform-based restrictions such as removal from monetization programs. Novelty: The study connects traditional legal norms on public order and exploitation with emerging digital behaviors on live streaming platforms. Implications: Strengthening law enforcement, regulatory oversight, and community awareness is essential to protect vulnerable populations and ensure accountability for both content creators and service providers in the digital environment. Highlights: Virtual gift solicitation involving marginalized individuals can constitute unlawful conduct under multiple statutes. Sanctions extend beyond criminal punishment to include civil claims and platform monetization restrictions. Regulatory oversight is necessary to safeguard at-risk populations within live streaming ecosystems. Keywords: TikTok Live; Online Begging; Vulnerable Groups; Legal Consequences; Digital Exploitation